Determination of bisphenol a in plastic bottles by using high performance liquid chromatography (hplc) / Ain Nur Syafiqah Sariman - Sariman, Ain Nur Syafiqah (Faculty of Applied Sciences, 2017)
Bisphenol A (BP A) is an endocrine disrupters which is mainly used in the plastic industry. On the other words, it means that BPA is able to mimic or interfere with the body's hormones and disrupts the endocrine system. Therefore, it can affected the consumer's health. Thus, in this research, BP A was detected by using high performance liquid chromatography (HPLC) which equipped with UV detector and C 18 column as its stationary phase. The mobile phase was composed of 65 % acetonitrile and 35 % deionized water where the flow rate was set to 0.75 mL/min for solid phase extraction (SPE) and 1.0 mL/min for liquid liquid extraction (LLE). Other than that, UV wavelength and column temperature used was 230 nm and 30°C respectively. In this analysis, the detection of BPA by using different types of extraction were studied. SPE and LLE were conducted in order to extract the BPA in the plastic bottles. At the end of this analysis, the analytical method was validated according to various parameter such as calibration curve, limit of detection (LOD), limit of quantification (LOQ) and accuracy. The best linearity obtained was in the range of 0.5 ppm - 30 ppm and 10 ppm - 50 ppm with a good linear correlation coefficient was observed with R2 = 0.9943 and R2 = 0.963 . The value of LOD and LOQ obtained from the calculation was 0.0043 ppm and 0.0146 ppm respectively. From the analysis, it was shown that LLE was the best method that could extract the BPA in the plastic bottles whereas there was no BP A found in the samples by using SPE method.